Parental Conflict and Adolescent Sleep Problems: The Mediating Role of Anxiety - Ahmmed, Badhon; Khan, Ayesha (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to investigate the mediating role of anxiety in the relationship between parental conflict and adolescent sleep problems.Methods: A descriptive correlational design was employed using a sample of 404 adolescents from Pakistan, selected based on the Morgan and Krejcie table. Participants completed standardized questionnaires measuring perceived parental conflict, anxiety symptoms, and sleep disturbances. Data analysis was conducted using SPSS-27 for Pearson correlation analysis and AMOS-21 for Structural Equation Modeling (SEM). The assumptions of normality, linearity, and multicollinearity were confirmed prior to analysis. The SEM approach allowed for testing both direct and indirect pathways within the proposed mediation model.Findings: Results from Pearson correlation indicated significant positive associations between parental conflict and anxiety (r = .51, p < .001), anxiety and sleep problems (r = .55, p < .001), and parental conflict and sleep problems (r = .47, p < .001). The structural model demonstrated good fit indices (χ² = 204.38, df = 84, χ²/df = 2.43, GFI = 0.94, AGFI = 0.91, CFI = 0.96, TLI = 0.95, RMSEA = 0.059). SEM analysis showed that parental conflict significantly predicted anxiety (b = 0.38, p < .001) and sleep problems (b = 0.19, p < .001), while anxiety significantly predicted sleep problems (b = 0.42, p < .001). The indirect effect of parental conflict on sleep problems through anxiety was also significant (b = 0.16, p < .001), confirming the mediating role of anxiety.Conclusion: The findings indicate that anxiety is a significant mediator in the relationship between parental conflict and adolescent sleep disturbances. These results underscore the need for family-based and anxiety-focused interventions to address sleep problems in adolescents exposed to high-conflict home environments.